Performances of Homogeneous and Heterogenized Methylene Blue on Silica Under Red Light in Batch and Continuous Flow Photochemical Reactors - Lancel, Maxime; Gomez, Catherine; Port, Marc; Amara, Zacharias (Frontiers in Chemical Engineering, 2021)
Methylene blue was efficiently immobilized on silica micro- and nanoparticles by electrostatic interactions and the performances of the heterogenized photocatalysts were compared against the homogeneous conditions using the photooxidation of citronellol as a model reaction under red light, in a batch and a continuous flow photochemical reactor. In batch, the heterogeneous photocatalyst outperforms the homogeneous one, presumably due to kinetic and stability effects. The two catalytic systems are also compared in a flow reactor displaying improved mass transfer properties. We demonstrate that this results in a dramatic enhancement in photocatalyst stability, reactivity and productivity. This study highlights the importance of photocatalyst stability under homogeneous versus heterogenized conditions and in batch versus flow photochemistry.